(untitled) (Open Academia: Journal of Scholarly Research, 2025)
This article analyzes the effective cost management of a joint-stock company operating in the construction sector. Cost management involves effectively implementing strategy and ensuring resources and process discipline to ensure the highest possible levels of quality, reliability and productivity at the lowest overall cost. Organizations with the most effective cost management consistently and boldly apply the criteria of relevance and value to every day activity